4.4 Three Variables


x+y−z=0    x+2y−4z=0    2x+y+z=0


 


 


 


 

x+y−z=0    x−y−z=0    x+y+2z=0


 


 


 


 

a−2b+c=5    2a+b−c=−1    3a+3b−2c=−4


 


 


 


 

3x+2y+2z=3    x+2y−z=5    2x−4y+z=0


 


 


 


 

x+y+z=2    6x−4y+5z=31    5x+2y+2z=13


 


 


 


 

−2x+y−3z=1    x−4y+z=6    4x+16y+4z=24


 


 


 


 

4x−3y+2z=40    5x+9y−7z=47    9x+8y−3z=97


 


 


 


 

3x+y−z=11    x+3y=z+13    x+y−3z=11


 


 


 


 

x+2y−z=4    4x−3y+z=8    5x−y=12


 


 


 


 

w+x−y+z=0    −w+2x+2y+z=5    −w+3x+y−z=−4    −2w+x+y−3z=−7